2011
DOI: 10.1111/j.1532-950x.2011.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Ventroversion with Double Pelvic Osteotomy Versus Triple Pelvic Osteotomy: A Cadaveric Study in Dogs

Abstract: A 25° DPO is most similar in acetabular ventroversion to 20° TPO (concordance correlation, 0.902).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 13 publications
4
34
0
Order By: Relevance
“…We utilized a 25° DPO plate because this is the implant that is used most commonly in clinical cases (22). Previous studies have determined that the degree of rotation of the acetabular segment is approximately five degrees less than the angle of the bone plate (1,22,26). Based on our data, the acetabular ventroversion achieved with the DPO technique is less than that previously described (1,26).…”
Section: Discussionsupporting
confidence: 44%
“…We utilized a 25° DPO plate because this is the implant that is used most commonly in clinical cases (22). Previous studies have determined that the degree of rotation of the acetabular segment is approximately five degrees less than the angle of the bone plate (1,22,26). Based on our data, the acetabular ventroversion achieved with the DPO technique is less than that previously described (1,26).…”
Section: Discussionsupporting
confidence: 44%
“…Because of the retrospective nature of this study, arthroscopic assessment of the coxofemoral joints was not available for analysis. Ventrodorsal radiographs have a low sensitivity compared with arthroscopy for detection of cartilage lesions . The combination of radiographic and arthroscopic findings could give a more complete assessment of the osseous, cartilaginous, and soft tissue structures of the coxofemoral joint.…”
Section: Discussionmentioning
confidence: 99%
“…In the authors' experience, TPO can result in a significant alteration in hip conformation. This rarely occurs after DPO, which results in less alteration of acetabular inclination and ventroversion after DPO compared with TPO . A larger cohort of dogs, in particular untreated dogs, would be required to definitively demonstrate that DPO leads to improvement in osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In growing dogs, the aim of the surgical treatment is to increase acetabular coverage to improve joint congruity. [1][2][3][4][5][6][7] Triple pelvic osteotomy (TPO) increases acetabular coverage of the femoral head by ventrolateral rotation of the dorsal acetabular rim following osteotomy of the ilium, ischium and pubis. [1][2][3][4] Ideal TPO candidates are infants 6 to 7 months of age with a dorsal acetabular rim slope of 20°, minimal damage to the acetabular rim and angles of reduction and subluxation of 25 and 5°, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…16 In this radiographic study, the dorsal acetabular coverage obtained with the 25°DPO technique was similar to the coverage obtained with 20°TPO. 16 In 2011, in a tomodensitometric study, Punke and colleagues demonstrated that a 25°DPO achieved very similar acetabular ventroversion to a 20°TPO 6 and it was suggested that DPO might represent an evolution of the TPO. 5,6,16 DPO resulted in a lower surgical complication rate than TPO in one study: 3.5% rate of implant failure, 9.4% screw pull-out rate for the caudal portion of the plate, one broken plate, one caudal iliac segment fracture, transient neurological deficit in two cases and four cases of incomplete ischial fractures.…”
Section: Introductionmentioning
confidence: 99%